Electro-Whirling Stir Casting: a Novel Approach for Fabricating Al7075/SiC MMCs with Enhanced Thermal Characteristics - Kumaraswamy, J.; Anil, K. C.; Canbay, Canan Aksu; Shivakumar, N. D. (Springer, 2024)
In the current research work, Al7075 reinforced with SiC particles of various configurations has been processed by adopting the stirred casting technique. Energy dispersive spectrometer tests have authenticated that the processed compounds are made up of Al7075 and SiC. The composition of SiC has been used in varied concentration of 0, 3, 6, 9 and 12% by weight and added to Al7075. An optical microscopy study has been carried out to identify the configuration of the composite material. In this study, we have attempted to examine the microstructures and thermal behavior of SiC-reinforced composites with different weight fractions. The microstructure, thermal conductivity enhanced 16.5% and coefficient of thermal expansion reduced 30.33% after adding SiC to Al7075. Al7075 reinforced with SiC particles exhibited better thermal properties than without SiC reinforcement.
Keywords: Al7075; SiC, thermal conductivity; Coefficient of thermal expansion